Kepatuhan Minum Obat Kelasi Besi, Konsumsi Sumber Protein Serta Zat Besi Melalui Pendampingan Individu Pada Pasien Anak Thalasemia Mayor (Case Series) (Studi Di Kota Banjarbaru Dan Sekitarnya) - Heldawati, Heldawati; Abdurrachim, Rijanti; Mahpolah, Mahpolah (Jurnal Skala Kesehatan, 2023)
The therapy given to Thalassemia patients with regular transfusions is iron chelation. One of the non-adherence in taking drugs regularly is a lack of understanding of the importance of drugs. Objectives: to determine adherence to taking iron chelation drugs, consumption of protein and iron sources through individual mentoring in thalassemia major pediatric patients in the city of Banjarbaru. Methods: Descriptive observational study with case series design of thalassemia major patients aged 5-18 years, residing in the city of Banjarbaru who received iron chelation therapy. Sampling using total sampling with 6 cases. The method of collecting data was by interviewing using a questionnaire. Data analysis used univariate analysis, descriptively in series and in depth. Results: There were 6 thalassemia patients with 50% of the patients aged 6-9 years, 66.7% of the patients were male, 66.7% of the nutritional status of the patients were normal, 50% of the children had primary education/equivalent, 66.7% of mothers and 50% of the patient's fathers have junior high and high school education/equivalent. Compliance with taking iron chelation drugs in the pretest in the lowlevel category (66.7%) and posttest in the low level category (66.7%). Consumption of protein sources during the pretest in the frequent category (66.7%) and the posttest in the frequent category (66.7%). Consumption of iron sources of patients during pretest in the frequent category (66.7%) and posttest in the rare category (66.7%). Keyword: Iron Chelation; Protein; Iron; Thalassemia Major